Cousteau: an unauthorized biography - Comber, Kevin; Cousteau, Jacques (Jacques-Yves), 1910-1997; Era Publications (Adelaide, South Australia Era Publications, 1992)
A concise biography of Jacques Cousteau, detailing his life as an oceanographer, filmmaker, and environmentalist, highlighting his contributions to marine exploration and conservation.
Includes bibliographical references
Middle school students
Keywords: Cousteau, Jacques, 1910-1997-Oceanographers-Marine Scientists-Environmentalists